PEMURNIAN CATECHIN DARI GAMBIR KOTO PANJANG, PESISIR SELATAN - Norman Ferdinal (Universitas Andalas, 2011)
Vol 5 No 1ABSTRACT The research about catechin purification from gambier was purposed to find its solubility properties in various solvent such as in cold water, hot water, hexane, ethyl acetate, and methanol. By knowing its solubility properties, the easiest way to purify the catechin could be gotten which is yielding about 7.33%. Further, the molecular structure has been gotten by determining its melting point and using spectrophotometric measurements such as UV, IR, 1H NMR, 13C NMR. Based on those measurements, d-cathecin structure with a melting point of 175 - 177 ºC was founded. The expected benefit from this research is it could be benefiting the development of gambier purification industry in order to enhancing added value of West Sumatera’s commodities. It would make Western Sumatera gaining stronger bargaining position due to the capability on selling not only on the crude form to abroad. The result of this research has indicated that catechin purification can be performed using an organic solvent and water. Keywords: Purification, catechin, gambier